2012
DOI: 10.1002/jpln.201100195
|View full text |Cite
|
Sign up to set email alerts
|

The effects of arsenic on the growth and nutritional status of Anadenanthera peregrina, a Brazilian savanna tree

Abstract: Anadenanthera peregrina is a Brazilian savanna tree species that occurs naturally in arsenic (As)‐contaminated areas, and its As resistance has been associated with arbuscular mycorrhizal–fungi (AMF) symbiosis. A plant's ability to survive in stressful environments is correlated with its nutrition status, which can be affected by As uptake. The present study evaluated the influence of As on the concentrations and distribution of nutrients in the roots and shoots of A. peregrina grown in the absence of AMF. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 33 publications
1
7
1
2
Order By: Relevance
“…Dias et al (2010) also found that As may be translocated to twigs in some plant species. In summary, As is a very important metalloid not only very toxic for plants but also influences the metabolism of the other elements such as N, P, K, Ca and Mg (Tu and Ma, 2005;Gomes et al, 2012). We suggested that As accumulator tree species may been used safely for urban-planning especially in highlycontaminated areas with As.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Dias et al (2010) also found that As may be translocated to twigs in some plant species. In summary, As is a very important metalloid not only very toxic for plants but also influences the metabolism of the other elements such as N, P, K, Ca and Mg (Tu and Ma, 2005;Gomes et al, 2012). We suggested that As accumulator tree species may been used safely for urban-planning especially in highlycontaminated areas with As.…”
Section: Discussionmentioning
confidence: 96%
“…In plant roots As compounds are sequestered in vacuoles and chelated with thiols and as a result of this the transportation of As compounds are limited (Zhao et al, 2010;Gomes et al, 2012). Zhao et al, (2010) also stated that As has low mobility and translocation from roots to aboveground parts of plants were limited except for hyper accumulator species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most plants are able to uptake As mainly in roots (Gomes et al 2012 ; Parraga-Aguado et al 2014 ), and only selected plant species such as Pteris vittata are characterized by effective uptake and translocation of As (Su et al 2008 ; Wang et al 2002 ). The general model of As uptake in the tree species studied in this and in the previous paper (Budzyńska et al 2017b ) is the same as for the majority of plants described in literature data (Li et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%